Efeitos da dieta cetogênica na promoção da tumorigênese colorretal induzida em ratos - Carvalho, Michele Oliveira (2022)
Lifestyle is strongly related to the quality and length of life, and food is one of the factors that can positively influence the development of diseases when the eating pattern is based on processed foods, refined foods, rich in saturated and trans fats and sugars. Although the global average life expectancy has increased in recent years, life quality has decreased due to the increase in chronic non-communicable diseases (NCDs), including cancer. Colorectal cancer (CRC), the third most diagnosed cancer worldwide, is a tumor type that brings serious consequences to longevity, since the incidence and prevalence rates have increased in young individuals even though it is common in people over 70 years old. The occurrence of CRC has been associated with a lifestyle based on low-fiber diets, excessive consumption of red meat, and saturated fats. The ketogenic diet (KD) has been strongly associated in the context of cancer prevention, as well as an important adjuvant to cancer treatment. It is characterized by its high fat content, sufficient protein for maintenance of activities and low carbohydrate content, which enables the use of fatty acids as an energy source, through the production of ketone bodies. Used for the treatment of epilepsy and nervous system disorders, KD has demonstrated, almost empirically, effects on carcinogenesis by directing anaerobic glucose (Warburg effect) modulating insulin levels. In this regard, the present study aimed to evaluate the effects of KD in the promotion of induced colorectal tumorigenesis in rats. The study was performed using two diet models: one based on a lipid profile rich in saturated fats (KD) and another rich in medium-chain triglycerides and lipid profile still rich in unsaturated fats (MCTKD). In vitro analyses were performed to determine antioxidant potential and total flavonoid and phenolic content. In vivo, preneoplastic lesions were induced in the colon of Wistar rats with the carcinogen 1,2 dimethylhydrazine [DMH 40mg/kg body weight (b.w.).] for 6 weeks. Immediately after the induction of lesions, the animals were subjected to the two diet models for 6 weeks. The animals were monitored daily for weight, abdominal circumference, naso-anal length, water, feed and diet consumption. After treatment, to evaluate the safety and chemopreventive potential, Aberrant Crypt Foci (ACF) and Aberrant Crypts (AC) in the colonic mucosa were quantified. The study of possible mechanisms involved in the chemopreventive effect was performed by employing immunohistochemical labeling for cyclooxygenase (COX- 2), Cell Proliferation Nuclear Antigen (PCNA) and β-catenin. Measurements of glucose and ketosis levels were performed before the start and at the end of the experimental period. Our results showed that the ketogenic profiles did not show antioxidant potential. None of the treatments were shown to influence body composition and monitoring of water and feed intake indicated no toxicity. The ketogenic profiles induced the body to a state of ketosis without modulating glucose levels and were able to reduce chromosomal damage in the bone marrow caused by the carcinogen DMH. Colonic mucosa analyses demonstrated that both diets were able to reduce the frequency of ACF and AC and that the most evident chemopreventive effect was observed in the MCTKD group. MCTKD group shows the relevance of the quality of the lipid profile for the protective effect. Data obtained in the immunohistochemistry assay showed that the diets act in the regulation of the inflammatory activity of COX2 and also in pathways of proliferation and transcriptional modulation as the Wnt/β-catenin pathway and Cell Proliferation Nuclear Antigen (PCNA). In the experimental conditions evaluated, the results suggest that ketogenic profiles have effects on different pathways of colorectal carcinogenesis, which provides previous information for other studies that can safely and effectively recommend this nutritional strategy in the future, both for cancer patients and for risk groups.